Chromosome-level assembly of Lindenbergia philippensis and comparative genomic analyses shed light on genome evolution in Lamiales - Chen, Bao-Zheng; Li, Da-Wei; Luo, Kai-Yong; Jiu, Song-Tao; Dong, Xiao; Wang, Wei-Bin; Li, Xu-Zhen; Hao, Ting-Ting; Lei, Ya-Hui; Guo, Da-Zhong; Liu, Xu-Tao; Duan, Sheng-Chang; et al. (Frontiers in Plant Science, 2024)
Lamiales, comprising over 23,755 species across 24 families, stands as a highly diverse and prolific plant group, playing a significant role in the cultivation of horticultural, ornamental, and medicinal plant varieties. Whole-genome duplication (WGD) and its subsequent post-polyploid diploidization (PPD) process represent the most drastic type of karyotype evolution, injecting significant potential for promoting the diversity of this lineage. However, polyploidization histories, as well as genome and subgenome fractionation following WGD events in Lamiales species, are still not well investigated. In this study, we constructed a chromosome-level genome assembly of Lindenbergia philippensis (Orobanchaceae) and conducted comparative genomic analyses with 14 other Lamiales species. L. philippensis is positioned closest to the parasitic lineage within Orobanchaceae and has a conserved karyotype. Through a combination of Ks analysis and syntenic depth analysis, we reconstructed and validated polyploidization histories of Lamiales species. Our results indicated that Primulina huaijiensis underwent three rounds of diploidization events following the γ-WGT event, rather than two rounds as reported. Besides, we reconfirmed that most Lamiales species shared a common diploidization event (L-WGD). Subsequently, we constructed the Lamiales Ancestral Karyotype (LAK), comprising 11 proto-chromosomes, and elucidated its evolutionary trajectory, highlighting the highly flexible reshuffling of the Lamiales paleogenome. We identified biased fractionation of subgenomes following the L-WGD event across eight species, and highlighted the positive impacts of non-WGD genes on gene family expansion. This study provides novel genomic 3 resources and insights into polyploidy and karyotype remodeling of Lamiales species, essential for advancing our understanding of species diversification and genome evolution.